2016
DOI: 10.5935/0034-7280.20160004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ophthalmic emergencies in a public reference hospital in Pernambuco, Brazil

Abstract: Purpose: To evaluate ophthalmological emergencies in a public reference hospital in Pernambuco. Methods: Cross-sectional retrospective study with 26.358 patients attended in the ophthalmic emergency Altino Ventura Foundation, in the period january to june 2013. Data were collected using protocols based on electronic registration forms of ophthalmological emergency Results: It was observed that 52.5% of patients were male, 42.5% were aged 21-40 years; 90.8% were from the region metropolitan area of Recife; 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
1
1
4
Order By: Relevance
“…Our series reported a lower percentage of non-urgent visits (30%) compared to literature. This is partly due to a lower prevalence of infectious conjunctivitis (6.3%) and eyelid inflammation (1.7%) in our sample compared to other series (8.7-39.2%) 4,16,18 . A likely explanation for this may be that patients with symptoms of conjunctivitis are treated by their primary care physician or they self-medicate (a very common practice in our country).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our series reported a lower percentage of non-urgent visits (30%) compared to literature. This is partly due to a lower prevalence of infectious conjunctivitis (6.3%) and eyelid inflammation (1.7%) in our sample compared to other series (8.7-39.2%) 4,16,18 . A likely explanation for this may be that patients with symptoms of conjunctivitis are treated by their primary care physician or they self-medicate (a very common practice in our country).…”
Section: Discussioncontrasting
confidence: 65%
“…In Ireland, Fenton et al 6 reported that 80.9% of visits were non-urgent and Alotaibi et al 13 from Saudi Arabia reported that 50.4% of visits were non-urgent (dry eye, chalazion, blepharitis, and allergic conjunctivitis). In Latin America, a series in Brazil 16 reported that 55% of eye-related visits were considered non-urgent and in Cuba 17 , 70.9% were considered non-urgent. Our series reported a lower percentage of non-urgent visits (30%) compared to literature.…”
Section: Discussionmentioning
confidence: 99%
“…En Irlanda, Fenton, et al 6 informaron que el 80.9% de las visitas no eran urgentes, y Alotaibi, et al 13 , de Arabia Saudita, informaron que el 50.4% de las visitas no eran urgentes (ojo seco, chalazión, blefaritis y conjuntivitis alérgica). En América Latina, una serie en Brasil 16 informó que el 55% de las visitas relacionadas con los ojos se consideraron no urgentes y, en Cuba 17 , el 70.9% se consideró no urgente. Nuestra serie informó un menor porcentaje de visitas no urgentes (30%) en comparación con la literatura.…”
Section: Discussionunclassified
“…Nuestra serie informó un menor porcentaje de visitas no urgentes (30%) en comparación con la literatura. Esto se debe en parte a una menor prevalencia de conjuntivitis infecciosa (6.3%) y blefaritis (1.7%) en nuestra muestra en comparación con otras series (8.7-39.2%) 4,16,18 . Una explicación probable para esto puede ser que los pacientes con síntomas de conjuntivitis son tratados por su médico de atención primaria o se automedican (una práctica muy común en nuestro país).…”
Section: Discussionunclassified
See 1 more Smart Citation